Reference Evapotranspiration Estimation in Climate Change Scenarios for Rio Verde in the State of Goiás, Brazil - Santos, Lucas da Costa; Bender, Fabiani Denise; Reis, Elton Fialho dos; Cruz, Guilherme Henrique Terra; Capuchinho, Frank Freire (Revista Geama, 2017)
Long-term changes in evapotranspiration can have extreme effects in hydrological processes as well as crop yields. The objective of this study was to quantify the expected changes in evapotranspiration in climate change scenarios using the Penman Monteith/FAO56 (PM) standard method and empirical equations for estimating reference evapotranspiration (ET0), specifically for the conditions of Rio Verde, in the state of Goiás, Brazil. Data from the National Institute of Meteorology, and Meteorology and Hydrology System of the State of Goiás were used to estimate the ET0 by using the following methods: Modified Penman, Radiation, Blaney-Criddle, Hargreaves-Samani, and Priestley-Taylor and Turc, which were compared with the PM method on the daily scale. From the ET0 obtained in each of these methods, their performance was evaluated through statistical indices in four future climate scenarios. The projections originated from two emission scenarios based on the HadGEM2-ES global climate model with medium (2040-2069) and long (2070-2099) term scenarios. The results presented that the Radiation and Turc methods are currently—and can be under the predicted conditions of future climate scenarios—the best options for estimation of ET0 in Rio Verde, when meteorological data are not available to implement the PM method. The Modified Penman and the Hargreaves-Samani methods should not be considered for estimating ET0 in the location evaluated.